Longitudinal evidence on treatment discontinuation, adherence, and loss of hypertension control in four middle-income countries - Mauer, Nicole; Geldsetzer, Pascal; Manne-Goehler, Jennifer; Davies, Justine I.; Stokes, Andrew C.; McConnell, Margaret; Ali, Mohammed K.; Winkler, Volker; Sudharsanan, Nikkil (Science translational medicine, 2022)
Managing hypertension is a highly dynamic process, yet current evidence on hypertension control in middle-income countries (MICs) is largely based on cross-sectional data. Using multiple waves of population-based cohort data from four MICs (China, Indonesia, Mexico, and South Africa), we undertook a longitudinal investigation into how individuals with hypertension move through care over time. We classified adults aged 40 years and over (N = 8527) into care stages at both baseline and follow-up waves and estimated the probability of transitioning between stages using Poisson regression models. Over a 5- to 9-year follow-up period, only around 30% of undiagnosed individuals became diagnosed [Mexico, 27% (95% confidence interval: 23%, 31%); China, 30% (26%, 33%); Indonesia, 30% (28%, 32%); and South Africa, 36% (31%, 41%)], and one in four untreated individuals became treated [Indonesia, 11% (10%, 12%); Mexico, 24% (20%, 28%); China, 26% (23%, 29%); and South Africa, 33% (29%, 38%)]. The probability of reaching blood pressure (BP) control was lower [Indonesia, 2% (1%, 2%); China, 9% (7%, 11%); Mexico, 12% (9%, 14%); and South Africa, 24% (20%, 28%)] regardless of treatment status. A substantial proportion of individuals discontinued treatment [Indonesia, 70% (67%, 73%); China, 36% (32%, 40%); Mexico, 34% (29%, 39%); and South Africa, 20% (15%, 25%)], and most individuals lost BP control by follow-up [Indonesia, 92% (89%, 96%); Mexico, 77% (71%, 83%); China, 76% (69%, 83%); and South Africa 45% (36%, 54%)]. Our results highlight that policies solely aimed at improving diagnosis or initiating treatment may not lead to long-term hypertension control improvements in MICs.
Gesehen am 21.02.2023